Determinants of higher education students’ willingness to pay for violent crime reduction: a contingent valuation study - Aurora A.C. Teixeira
By eliciting an individual’s Willingness to Pay (WTP) for a reduction in crime risks, the contingent valuation method is one of the most solid methodologies in use to estimate the intangible costs of crime. However, very few studies have applied contingent valuation methods to random samples of the population located in high crime rate areas. This study is, to the best of our knowledge, the first attempt to apply the contingent valuation method to estimate how much a specific group of society, which is relatively prone to falling victim to (violent) crime, i.e., students, is willing to pay to reduce the likelihood of being the victim of violent crime. In contrast to the existing literature, our study focuses on a rather unexplored context, Portugal, where criminality and violent crime rates are relatively low by international standards, even though they have been on the rise. Based on responses from 1122 higher education students in a broad range of degrees (from Economics to Psychology and the Humanities), we found that 33% of our respondents have been victims of crime in the past, although in general they did not result in physical or psychological injuries. A reasonable percentage of the students (almost 40%) is very worried about falling victim to a crime and 52.8% worries moderately. Over 40% of our respondents were willing to pay a certain amount but less than 50€, whereas 20.8% were willing to pay between 50€ and 250€. On average, all other determinants constant, younger and female students revealed that they were more inclined to pay so as to avoid violent crime than their older and male counterparts. Low and high income Portuguese students do not differ in their willingness to pay more to avoid being victims of violent crime. Cautious behaviour, such as locking doors at home, and a strong opinion about policies and payment vehicles with potential to reduce the risk of crime is positively associated with the WTP. Finally, the students’ field of study surfaced as a key determinant of WTP – students enrolled in Economics and Management revealed a higher WTP. Such findings are likely to have a critical impact on crime and insurance policies.Contingent Valuation Method; Intangible costs; Crime costs